Effects of temperature and microbial disruption on juvenile kelp Ecklonia radiata and its associated bacterial community - Vadillo Gonzalez, Sebastian; Hurd, Catriona L.; Britton, Damon; Bennett, Eloise; Steinberg, Peter D.; Marzinelli, Ezequiel M. (Frontiers in Marine Science, 2024)
Ocean warming can affect the development and physiological responses of kelps, and under future climate change scenarios, increasing seawater temperatures pose a major threat to these habitatforming species. However, little is known about the effects of warming on epiphytic bacterial communities and how an altered microbiome may interact with temperature stress, affecting the condition and survival of kelp, particularly of the potentially more vulnerable early life stages. Here, we tested the effects of thermal stress on the growth and physiological responses of juvenile kelp Ecklonia radiata in which their epiphytic bacterial community was experimentally disrupted using antimicrobials, simulating dysbiosis. We hypothesized that, under thermal stress (23 °C, simulating a extreme scenario of ocean warming in Tasmania), kelp with a disrupted bacterial community would be more strongly affected than kelp with an undisrupted microbiome or kelp under ambient temperature (14 °C) but with a disrupted microbiota. Thermal stress reduced growth, increased tissue bleaching and negatively affected net photosynthesis of kelp. In addition, a substantial change in the epiphytic bacterial community structure was also found under thermal stress conditions, with an increase in the abundance of potentially pathogenic bacterial groups. However, microbial disruption did not act synergistically with thermal stress to affect kelp juveniles. These results suggest that effects of elevated temperature on juvenile kelps is not microbially-mediated and that juveniles may be less susceptible to disruptions of their microbiome.